IMPLIKASI PENURUNAN EKSPOR GAMBIR INDONESIA KE INDIA TERHADAP PEREKONOMIAN MASYARAKAT KABUPATEN LIMA PULUH KOTA (Studi Kasus : Penurunan Ekspor Gambir Kabupaten Lima Puluh Kota, Sumatera Barat Tahun 2008-2012) - Vina Rahmadini; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the implications that occurred as the result of gambier exports reduction from Indonesia to India toward community economy of Lima Puluh Kota district in the year 2008 – 2012. Gambier is one of the crops that has an important role in the economy of the local community, but in recent years, there is a decline in the value of exports. So the reseacher ask a question, what is the impact of decline in the value of gambier exports from Indonesia to India to community economy of Lima Puluh Kota district.This research uses descriptive research methods and also using primary and secondary data. The writer got primary data through direct observation and interview. While the secondary data was collected through the study to library with reference of books, journals, articles, bulletins, newspapers and other news from the relevant media. This research uses the perspective of liberalism with international trade theory and export base to explain the implications of the decline in exports that happened.The results of this research indicate that the implications of the decline in gambier export from Lima Puluh Kota district to India has the impact to community economy in Lima Puluh Kota district and distribution sequence characterized by the increasing the number of poor, agricultural land cover gambier and reduced income of Lima Puluh Kota district.Keywords: Implications, Exports, Gambier, Economic, Downturn